2022
DOI: 10.1101/2022.12.14.520410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptual awareness is gradual in temporal and dichotomous in fronto-parietal cortices

Abstract: Two major issues in consciousness research concern the measuring methods that determine per-ceptual unawareness and whether consciousness is a gradual or an "all-or-nothing" phenomenon. This 7T fMRI study addresses both questions using a continuous flash suppression paradigm with an emotional recognition task (fear vs neutral bodies) in combination with the perceptual awareness scale. Behaviorally, recognition sensitivity increased linearly with increased stimuli awareness and was at chance level during percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 145 publications
0
1
0
Order By: Relevance
“…A related study investigating facial expressions found that recognition of fearful faces was the least accurate and the slowest among seven emotion categories (Calvo and Lundqvist, 2008). Similarly, Poyo Solanas et al (2022) associated freezing behavior with slower heart rate when participants were exposed to fearful compared to neutral body expressions in conditions of reduced visual awareness. Moreover, several studies reported suppression of motor readiness following exposure to fearful body expressions (Borgomaneri et al, 2015;Borgomaneri, Vitale and Avenanti, 2017).…”
Section: Affective and Feature-based Determinants Of Awarenessmentioning
confidence: 92%
“…A related study investigating facial expressions found that recognition of fearful faces was the least accurate and the slowest among seven emotion categories (Calvo and Lundqvist, 2008). Similarly, Poyo Solanas et al (2022) associated freezing behavior with slower heart rate when participants were exposed to fearful compared to neutral body expressions in conditions of reduced visual awareness. Moreover, several studies reported suppression of motor readiness following exposure to fearful body expressions (Borgomaneri et al, 2015;Borgomaneri, Vitale and Avenanti, 2017).…”
Section: Affective and Feature-based Determinants Of Awarenessmentioning
confidence: 92%